Macroeconomic imbalances: a question of trust? - Sascha Buetzer; Christina Jordan; Livio Stracca (European Central Bank (ECB), 2013)
In this paper, we address the question of whether cross-country differences in civic capital, notably interpersonal trust, have contributed to the build-up of macroeconomic imbalances over the last three decades. We analyse the link between a stylised index of economic imbalances (a combination of the government budget balance, the inflation rate and the current account balance) and interpersonal trust, alongside other measures of civic and cultural capital, obtained from value survey data for 65 advanced and emerging countries. For the whole set of countries, we find robust empirical evidence for a negative and significant relationship between trust and macroeconomic imbalances which may therefore partly reflect underlying heterogeneity in civic capital. Within the euro area, differences in trust exist although they are not particularly large from an international perspective. With the nexus between trust and macroeonomic imbalances being equally robust we can attribute one fifth of the variation in intra-euro area imbalances to differences in interpersonal trust. Euro area membership and EU fiscal rules do not appear to have weakened the link between the two variables.
Keywords: F33; F42; Z1; 330; culture; euro area; Macroeconomic imbalances; Trust